Nivel de conocimientos y manejo de métodos anticonceptivos en adolescentes del Centro de Salud 7 de octubre, Quevedo. noviembre 2023 - abril 2024. - Pozo Fernández, Melissa Elina (2024)
According to the National Institute of Statistics and Censuses, in 2022, 38,087 live births were obtained from mothers between 15 and 19 years old, which corresponds to a rate of 47.3 live births per 1,000 women in that age range. The number of pregnant adolescents who go to the 7 de Octubre health center is significant, as is the percentage of adolescents who attend for a contraceptive method and do not have monitoring of its use. The present research aims to evaluate in detail the level of knowledge and use of contraceptive methods (CAM) among adolescents who attend the 7 de Octubre Health Center in Quevedo during the period from November 2023 to April 2024. The use of CAM affects their sexual and reproductive health, understanding these aspects is crucial to identify possible gaps in sexual education and health services available for this population. The project used a Quantitative methodology, inductive-deductive method of descriptive, applied, prospective and field type. Having as a population the adolescents who attended the health center in the period from November 2023 to April 2024, a universe of 65 adolescents was obtained, which, using inclusion and exclusion criteria, a sample of 45 adolescents was selected, the study instrument applied The survey consisted of 15 questions, the results were recorded in a database created in an Excel spreadsheet.